Dynamics and limitations of phytoplankton biomass along a gradient in Mwanza Gulf, southern Lake Victoria (Tanzania). (17th October 2013) - Cornelissen, I. J. M.; Silsbe, G. M.; Verreth, J. A. J.; van, E.; Nagelkerke, L. A. J.
Summary We investigated how dynamics in phytoplankton biomass are driven through light and nutrient limitations in the Mwanza Gulf, Lake Victoria (Tanzania). We measured light attenuation, chlorophyll a and water quality parameters along a phytoplankton biomass gradient in the Mwanza Gulf at six sampling stations in three different seasons from August 2009 to March 2011. We found a higher rate of attenuation of photosynthetic available radiation than in other gulfs of Lake Victoria which could only partially be explained by phytoplankton biomass, measured as chlorophyll a. Suspended particulate detritus strongly affected light attenuation, particularly in shallow water. In shallow water in the southern part of the Mwanza Gulf, nutrients were in excess and phytoplankton biomass was limited by light. In deeper water near the entrance of the gulf, light was not limiting when nitrogen probably was, as indicated by the N:P ratio. Low abundance of N‐fixing phytoplankton species suggests that N‐fixation was low in shallow water. Phytoplankton biomass was lower in Mwanza Gulf than in northern gulfs of Lake Victoria, but might increase in the future as a result of nutrient enrichment caused by an increase in intensive agriculture and rapid growth of the city of Mwanza.